RNA Binding Proteins RZ-1B and RZ-1C Play Critical Roles in Regulating Pre-mRNA Splicing and Gene Expression during Development in Arabidopsis. Issue 1 (31st December 2015) - Wu, Zhe; Zhu, Danling; Lin, Xiaoya; Miao, Jin; Gu, Lianfeng; Deng, Xian; Yang, Qian; Sun, Kangtai; Zhu, Danmeng; Cao, Xiaofeng; Tsuge, Tomohiko; Dean, Caroline; et al.
Abstract : Plant-specific RNA binding proteins RZ-1B and RZ-1C interact with a number of highly conserved serine/arginine-rich proteins to regulate RNA splicing and gene expression in Arabidopsis. Abstract: Nuclear-localized RNA binding proteins are involved in various aspects of RNA metabolism, which in turn modulates gene expression. However, the functions of nuclear-localized RNA binding proteins in plants are poorly understood. Here, we report the functions of two proteins containing RNA recognition motifs, RZ-1B and RZ-1C, in Arabidopsis thaliana . RZ-1B and RZ-1C were localized to nuclear speckles and interacted with a spectrum of serine/arginine-rich (SR) proteins through their C termini. RZ-1C preferentially bound to purine-rich RNA sequences in vitro through its N-terminal RNA recognition motif. Disrupting the RNA binding activity of RZ-1C with SR proteins through overexpression of the C terminus of RZ-1C conferred defective phenotypes similar to those observed in rz-1b rz-1c double mutants, including delayed seed germination, reduced stature, and serrated leaves. Loss of function of RZ-1B and RZ-1C was accompanied by defective splicing of many genes and global perturbation of gene expression. In addition, we found that RZ-1C directly targeted FLOWERING LOCUS C ( FLC ), promoting efficient splicing of FLC introns and likely also repressing FLC transcription. Our findings highlight the critical role of RZ-1B/1C in regulating RNA splicing, gene expression, and many key aspects of plant development via interaction with proteins including SR proteins.